CAPABILITIES, GROWTH AND NON-AGRARIAN VILLAGES : Second Phase of the Kerala Model - Narendar Pani Jafar K (NATIONAL INSTITUTE OF ADVANCED STUDIES, 2008)
Kerala's image of a low growth state with high social indices has come up against some striking empirical trends. Its growth rate has taken off, it has become vastly less agrarian and has yet refused to urbanize. This paper seeks to explain these patterns asa result of the state's limited use of the capabilities approach. We use a combination of a simple mathematical model and the experience of Kerala to argue that the capabilities approach can affect patterns of growth as well as the transition of agrarian economies into non-agrarian ones. This in turn can affect the process of urbanization, contributing to the creation of nonagrarian villages